STUDENTS REFLECT ON THEIR CHALLENGES WITH AN INTERVIEW ASSIGNMENT: ADVICE ON THE INCORPORATION OF INTERVIEW ASSIGNMENT IN A FIRST YEAR UNIVERSITY COURSE - Rose, Janine (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This paper explores students’ reactions to an immigrant interview project that was included in a Black immigrant experiences course. The immigrant interview project asked students to explore the usefulness of personal stories for the examination of Black immigrant experiences in Canada by completing a short interview with a Black Canadian immigrant. Students were also expected to include an in-depth analysis of how aspects of the immigrant’s life relate to central issues, themes and concepts covered in the course. The information in this presentation is based on written reflections that highlight what students learned from the experience of interviewing a Black immigrant as a course assignment. The reports shows that students were intrigued and also nervous about the novel opportunity to interview a black immigrant. Additionally, they felt that learning about immigration experiences was best acquired through speaking to a real immigrant. The presentation will highlight challenges that students encountered with this assignment and strategies that instructors may consider when developing an assignment of this nature for their own courses.